2017
DOI: 10.1186/s12882-017-0491-z
|View full text |Cite
|
Sign up to set email alerts
|

Simple, readily available clinical indices predict early and late mortality among patients with ANCA-associated vasculitis

Abstract: BackgroundThe early identification of patients with ANCA-associated vasculitis (AAV) who are at increased risk for inferior clinical outcome at the time of diagnosis might help to optimize the immunosuppressive therapy. In this study we wanted to determine the predictive value of simple clinical characteristics, which may be applicable for early risk-stratification of patients with AAV.MethodsWe retrospectively analyzed the outcome of 101 consecutive patients with AAV receiving a protocolized immunosuppressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Most patients had ≥1 comorbidity at diagnosis confirming results of previous studies [3,17,18] who also found that majority of patients had comorbid diseases including important cardiovascular diseases [18]. Some studies have demonstrated comorbidity at diagnosis is one factor determining long term survival [17,18] but another study suggested the patients functional status, which would be influenced by comorbidity is more predictive [3].…”
Section: Response To Induction Therapysupporting
confidence: 81%
“…Most patients had ≥1 comorbidity at diagnosis confirming results of previous studies [3,17,18] who also found that majority of patients had comorbid diseases including important cardiovascular diseases [18]. Some studies have demonstrated comorbidity at diagnosis is one factor determining long term survival [17,18] but another study suggested the patients functional status, which would be influenced by comorbidity is more predictive [3].…”
Section: Response To Induction Therapysupporting
confidence: 81%
“…17 Resolution of hematuria was also considered criteria for remission. 15 Relapse was defined as an increase in serum creatinine level accompanied with GFR decline, new RBC cast above 5 cells, new proteinuria above 500 mg over 24 hours not explained by any other secondary causes, worsening or new extrarenal manifestations attributable to active vasculitis after a time of remission, with or without increase in ANCA titers. 12 Complications encountered (namely, infection required hospitalization, thrombotic events, malignancy and infertility) and disease outcomes were also recorded.…”
Section: Data Collectionmentioning
confidence: 99%
“…3,13 We hypothesized that the initial BVAS might be a valid independent measure that can estimate the future relapse as only few articles have evaluated the predictive value of BVAS for future relapses with ANCA associated vasculitis. 14,15 Birmingham Vasculitis Activity Score (BVAS) is a well-established and validated measurement tool for disease activity and extension, as BVAS=0 defines disease remission and BVAS≥1 defines active disease. 16 Consequently, the present retrospective analysis would explore the characters of AAV patients, with the correlates for increased relapses and complications, in addition to the ability of BVAS to a marker of impending disease relapse.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that comorbidities were associated with mortality, and this relationship remained independent of other important clinical characteristics [17]. We also analysed the relationship between comorbidities and the prognosis and renal outcome, while comorbidities were not independent predictors of death or ESRD or the doubling of serum creatinine.…”
Section: Discussionmentioning
confidence: 94%
“…MPA is a multiple-system disease, involving primarily the kidneys and lungs, and it is characterized by necrotizing glomerulonephritis and pulmonary capillaritis [11]. Many clinical indexes have been reported to have prognostic value in AAV patients, such as age [6, 12, 13], haemoglobin level [8], albumin level [14], Birmingham Vasculitis Activity Score (BVAS) [15, 16] and comorbidities [17]. Many studies have shown that AAV patients with worse renal function have a poorer prognosis [11, 13, 15, 18], including patients with MPA [14, 19].…”
Section: Introductionmentioning
confidence: 99%